2009
DOI: 10.1002/bdra.20619
|View full text |Cite
|
Sign up to set email alerts
|

Public health projects for preventing the recurrence of neural tube defects in the United States

Abstract: Only 15 states and Puerto Rico had or were planning NTD recurrence prevention projects. An NTD recurrence prevention project using minimal resources should consist of timely case ascertainment, educational materials, and mechanisms for disseminating these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The results of this study indicate that while there are similarities, these 2 clinical conditions are not synonymous. Limited studies (Coe et al., ; Collins et al., ; Doig et al., ; Frankel et al., ; Oesterheld et al, ; O'Malley et al., ; Snyder et al., ) suggest differences in treatment effectiveness between FASD and ADHD, thus further indicating the need for accurate identification of alcohol‐affected children.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicate that while there are similarities, these 2 clinical conditions are not synonymous. Limited studies (Coe et al., ; Collins et al., ; Doig et al., ; Frankel et al., ; Oesterheld et al, ; O'Malley et al., ; Snyder et al., ) suggest differences in treatment effectiveness between FASD and ADHD, thus further indicating the need for accurate identification of alcohol‐affected children.…”
Section: Discussionmentioning
confidence: 99%
“…However, we feel that our study and others 21 have shown that recurrence prevention is quite effective. Because only approximately one-third of states have or have had NTD recurrence prevention projects, 22 more public health agencies need to provide the funding and personnel to prevent the recurrence of NTDs in this very high risk population.…”
Section: Discussionmentioning
confidence: 99%
“…The failure in closure, which is initiated at multiple sites of the neural tube (O'Rahilly and Müller, 2002), results in a spectrum of cranial and spinal canal defects ranging from anencephaly to very minor vertebral defects either open or closed. Approximately 70% of NTDs are isolated and are presumed to be multifactorial in origin (Aguiar et al, 2003), thereby conferring a 3% recurrence risk for subsequent pregnancies (Collins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%